2012
DOI: 10.1530/eje-11-0840
|View full text |Cite
|
Sign up to set email alerts
|

Inositol administration reduces oxidative stress in erythrocytes of patients with polycystic ovary syndrome

Abstract: Objective: Possibly due to a deficiency of insulin mediators, polycystic ovary syndrome (PCOS) is often associated with insulin resistance (IR) and hyperinsulinemia, likely responsible for an elevated production of reactive oxygen species. We investigated oxidative-related alterations in erythrocytes and anti-inflammatory effects of inositol in women with PCOS before and after treatment with myo-inositol (MYO). Methods: Twenty-six normal-weight PCOS patients were investigated before and after MYO administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 46 publications
(61 reference statements)
2
55
0
Order By: Relevance
“…In the majority of cases, PCOS is a genetic disease related to insulin resistance, which predisposes to obesity, hypertension, preeclampsia, and metabolic syndrome. Insulin resistance is a characteristic of both obese and lean patients with PCOS . Treatment with healthy lifestyle, metformin, or inositol could prevent the progression to diabetes mellitus and metabolic and cardiovascular risk later in life.…”
Section: The Model Of Polycystic Ovary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of cases, PCOS is a genetic disease related to insulin resistance, which predisposes to obesity, hypertension, preeclampsia, and metabolic syndrome. Insulin resistance is a characteristic of both obese and lean patients with PCOS . Treatment with healthy lifestyle, metformin, or inositol could prevent the progression to diabetes mellitus and metabolic and cardiovascular risk later in life.…”
Section: The Model Of Polycystic Ovary Syndromementioning
confidence: 99%
“…Insulin resistance is a characteristic of both obese and lean patients with PCOS. 10 Treatment with healthy lifestyle, metformin, or inositol could prevent the progression to diabetes mellitus and metabolic and cardiovascular risk later in life. It is well known that these patients are predisposed to hypertension and preeclampsia, and, therefore, regulated salt intake is also important to reduce the risk associated with genetic predisposition.…”
Section: The Model Of Polycystic Ovary Syndromementioning
confidence: 99%
“…whole grains, seeds, and fruits) and also can be produced from glucose in the human body (Carlomagno and Unfer, 2011[10]). Evidence have shown that this nutrient could have a helpful role in decreasing the hormonal profile, oxidative abnormalities, and as well as the metabolic factors in patients with PCOS, probably due to the amelioration of insulin resistance in these patients (Costantino et al, 2009[13]; Donà et al, 2012[16]). In a placebo-controlled trial, women with PCOS were randomized to receive either oral myo-inositol (4 g/d) plus folic acid (400 mcg/d) or folic acid alone for 12-16 weeks (Costantino et al, 2009[13]).…”
Section: Nutrients and Pcosmentioning
confidence: 99%
“…Several studies have reported to date the positive effects of myo-inositol and D-chiro-inositol on clinical, metabolic, endocrine, hormonal, and oxidative abnormalities in women with PCOS. Based on these observations, this naturally occurring compound may represent an alternative or complementary care to metformin treatment in PCOS patients (Donà et al, 2012[16]).…”
Section: Nutrients and Pcosmentioning
confidence: 99%
“…PE is also characterized by increased inflammatory status, which may be promoted by the altered placental perfusion leading to the release of cytotoxic factors into the circulation, increased vascular tone, and endothelial dysfunction . The pro‐oxidative status is also present in PCOS and is involved in the increased metabolic, cardiovascular, and obstetric complications seen in the disease …”
Section: Pe: Interrelationship Between Insulin Resistance Inflammatimentioning
confidence: 99%